OPTIMIZATION OF CONSTRUCTION PRODUCT DISTRIBUTION NETWORK USING TRANSPORTATION SYSTEM DESIGN AND LINEAR PROGRAMMING APPROACH - Elfantoro, Indra; Dewi, Yulida Intani; Herdiana, Mochamad Rafi; Yasin, Rahmat; Wajdi, Muhammad Raihan (Politeknik META Industri Cikarang, 2025)
This study optimizes the construction product distribution network in the Jakarta area using a Transportation System Design approach and Linear Programming (MILP and VRP) implemented in Python programming. The primary goal is to minimize total travel distance, delivery time, and transportation costs without violating vehicle capacity constraints, customer demand, and operational time windows. Optimization results show a 30% reduction in total travel distance from 5,830 km to 4,061 km and transportation cost savings of up to 8.1% or approximately IDR 23 million per month. The computation process is efficient, completing in under 30 seconds, enhancing accuracy and reducing human error. This optimization supports on-time delivery, maintains product quality, improves customer satisfaction, and operational efficiency, including reduced fuel consumption and carbon emissions. Practical recommendations include setting a Minimum Order Quantity (MoQ), using larger capacity trucks, and improving real-time communication and vehicle tracking to support more effective distribution management in the construction industry